Oversimplifying Teaching of the Control of Variables Strategy - Lorch, Jr., Robert F., (Colegio Oficial de Psicólogos de Madrid, 2020)
Two experiments compared closely related interventions to teach the control of variables strategy (CVS) to fourth-grade students. Over the two experiments, an intervention first developed by Chen and Klahr (1999) was most effective at helping students learn how to design and evaluate single-factor experiments. In Experiment 1, attempts to reduce the cognitive load imposed by Chen and Klahr's basic teaching intervention actually produced poorer learning and transfer of CVS. In Experiment 2, attempts to simplify Chen and Klahr's algorithm for teaching students how to set up a valid experimental design also produced poorer learning and transfer of CVS. Both experiments illustrate that oversimplifying a domain or the logic behind controlling variables can undermine the effectiveness of an intervention designed to teach CVS.